Prevalence, determinants and impact of unawareness about the health consequences of tobacco use among 17 929 school personnel in 29 African countries - Agaku, Israel T (BMJ Publishing Group, 2014)
OBJECTIVES: To assess prevalence, determinants and impact of unawareness about the health consequences of tobacco use among school personnel in Africa. DESIGN: Cross-sectional surveys. SETTING: Twenty-nine African countries. PARTICIPANTS: Representative samples of school personnel from 29 African countries (n=17 929), using data from the 2006–2011 Global School Personnel Surveys. OUTCOME: We assessed if school personnel were aware of the following five facts about tobacco use: (1) tobacco use is addictive; (2) secondhand smoke exposure is harmful; (3) smoking causes lung cancer; (4) smoking causes heart disease and (5) smoking does not cause malaria. Using multivariate logistic regression, we measured the impact of unawareness of the health consequences of tobacco use on behaviour and attitudes towards tobacco control. RESULTS: A median of 62.6% of school personnel were unaware of at least one health consequence of tobacco use. School personnel in countries with mandatory cigarette health warning labels had lower odds of being unaware of any health consequence of tobacco use than countries where health warning labels were not mandatory (adjusted OR [aOR]=0.51; 95% CI 0.37 to 0.71). A significant dose–response relationship was seen between being ignorant of 1; 2; or ≥3 tobacco use health consequences respectively (compared with not being ignorant of any), and the odds of the following outcomes: non-support of bans on tobacco industry sponsorship of school or extracurricular activities (aOR=1.47; 1.91; and 2.98); non-support of bans on all tobacco advertisements (aOR=1.24; 1.78; and 2.68) and non-support of policies prohibiting tobacco use by school personnel on campus (aOR=1.79; 4.45; and 4.56). CONCLUSIONS: Unawareness of the health consequences of tobacco use was associated with poor support for tobacco control policies. Intensified efforts are needed in African countries to warn about the dangers of tobacco use.